Dinamika Ijtihad dalam Islam: Pertemuan Madrasah Ahlur Ra’yi dan Ahli Hadis - Rifka Siti Khuzaimah; Muhammad Husni Abdulah Pakarti; Diana Farid; Husain Husain; Ulummudin Ulummudin; Ais Surasa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
During the time of Rasulullah SAW, Muslims did not need certain rules in understanding sharia law. After the spread of Futuhat Islamiyah, Arab Muslims interacted a lot with other nations who had different languages. On the other hand, the need for ijtihad is very urgent, because there are many new problems that have never occurred before and require clarity in fiqh law. So two large madrasahs emerged that reflected their ijtihad method - the Ahlir-ra'yi Madrasah used more qiyas (analogies) to generate heated debates, thus making the ulama feel the need to create written regulations that were recorded as common law in uniting these two madrasas. The hadith about being more careful in giving fatwas and qiyas gave rise to heated debate, making the ulama feel the need to make written rules which were recorded as joint laws in uniting the two madrasas. Imam Syafi'i was the first person to write a book about ushul fiqh-Imam Syafii was a great mufti of the Muslim community who was also the founder of the Syafi'i school, developing his school in Baghdad. Ushul fiqh is the postulates of fiqh which are global in nature - The object of the discussion is to study the postulates which are still of a general nature seen from their general legal provisions and the ultimate aim of studying them is to protect the Islamic religion from deviations and misuse of the postulates of the Shari'a, so that misleading carelessness does not occur.